An electrochemical aptasensor based on DNA-AuNPs-HRP nanoprobes and exonuclease-assisted signal amplification for detection of aflatoxin B1. (March 2020) - Hui, Yuanyuan; Wang, Bini; Ren, Rong; Zhao, Aiqing; Zhang, Fuxin; Song, Shuanghong; He, Yaping
Abstract: It is very essential and meaningful for detection and quantitation of aflatoxin in food and agricultural commodities to establish a rapid and accurate detection method. Herein, a novel electrochemical aptasensor for sensitive and selective detection of aflatoxin B1 (AFB1 ) was successfully constructed. The thiolated complementary strand (cDNA) of the AFB1 aptamer (Apt) was immobilized on the surface of the glassy carbon electrode (GCE) modified with gold nanoparticles (AuNPs) through Au–S bond. Then Apt was attached on the surface of GCE via by specific base pairing. In the presence of AFB1, the Apt was detached from the electrode surface by specific recognition between the AFB1 and Apt, forming Apt-AFB1 conjugates in solution. The conjugates were digested by exonuclease I ( Exo I) to trigger AFB1 recycling. Finally, DNA-AuNPs-horseradish peroxidase (DNA-AuNPs-HRP) nanoprobes was bound with cDNA on the surface of electrode by specific base pairing. HRP could catalyze the oxidation of hydroquinone (HQ) to benzoquinone (BQ) by hydrogen peroxide (H2 O2 ) for producing a strong electrochemical signal. Under the optimized conditions, the electrochemical signals increased with increasing concentrations of AFB1 in a range from 10 −3 ng mL −1 to 200 ng mL −1 with a low detection limit of 3.3 × 10 −4 ng mL −1 . Moreover, the aptasensor has been successfully applied for the determination of AFB1 in peanuts and corn samples and the recoveries were 88.5 %–110.2%, which would provide a novel method for the rapid detection of AFB1 in food samples. Highlights: A novel electrochemical aptasensor was developed for the AFB1 . The developed aptasensor exhibited wide linear range and low detection limit to AFB1 . The aptasensor has been also successfully applied for the determination of AFB1 in peanuts samples.